Effects of the 2003 advertising/promotion ban in the United Kingdom on awareness of tobacco marketing: findings from the International Tobacco Control (ITC) Four Country Survey. (5th June 2006) - Harris, F; MacKintosh, A M; Anderson, S; Hastings, G; Borland, R; Fong, G T; Hammond, D; Cummings, K M
Abstract : Background: In February 2003, a comprehensive ban on tobacco promotion came into effect in the United Kingdom, which prohibited tobacco marketing through print and broadcast media, billboards, the internet, direct mail, product placement, promotions, free gifts, coupons and sponsorships. Objective: To investigate the impact of the UK's comprehensive ban on tobacco promotion on adult smokers' awareness of tobacco marketing in the UK relative to Canada, the United States and Australia. Design: A total of 6762 adult smokers participated in two waves of a random digit dialled telephone survey across the four countries. Wave 1 was conducted before the UK ban (October–December 2002) and Wave 2 was conducted after the UK ban (May–September 2003). Key measures: Awareness of a range of forms of tobacco marketing. Results: Levels of tobacco promotion awareness declined significantly among smokers in the UK after implementation of the advertising ban. Declines in awareness were greater in those channels regulated by the new law and change in awareness of tobacco promotions was much greater in the UK than the other three countries not affected by the ban. At least in the short term, there was no evidence that the law resulted in greater exposure to tobacco promotions in the few media channels not covered by the law. Notwithstanding the apparent success of the UK advertising ban and the controls in other countries, 9–22% of smokers in the four countries still reported noticing things that promoted smoking "often or very often" at Wave 2. Conclusions: The UK policy to ban tobacco advertising and promotion has significantly reduced exposure to pro-tobacco marketing influences. These findings support the effectiveness of comprehensive bans on advertising and promotion, as included in the Framework Convention on Tobacco Control.